Desplazamiento forzado por conflicto armado : una década de investigación en el eje cafetero (2013)
This text sets out a review of the studies that have been performed on forced displacement by armed conflict in the Coffee Zone from the years 1995 to 2010. This an inquiry was carried out of all available documents that treat the phenomenon. The formats were revised article, research project, report research findings and books. According to the results, the main topics addressed by researchers is: How are incorporated as displaced persons to the lifestyles of the recipient site, with six (6) research, also was found in the greatest number of Risaralda research, with a production of sixteen (16). The University of Caldas was the greatest research institution, with a total of nine (9). Among the decade from 1995 to 2005, the peak production years were: 2001, 2002 and 2003.